INVENSI DALAM GENRE WESTERN: ANALISIS FORMULA TERHADAP FILM WILD WILD WEST DAN DJANGO UNCHAINED [Inventions in Western Genre: Formula Analysis in Wild Wild West and Django Unchained Films] - - Andriadi (Kantor Bahasa Provinsi Maluku, 2016)
The degradation of appreciation toward Western movies nowdays became the backround of this research. The film producers tried to revitalize the elements of Western movies in order to produce more interesting films in different atmosphere. The problems of this research were to investigate inventions and cultural interaction to explore external elements which caused the changes of Western formulas in films Wild Wild West (1999) and Django Unchained (2012). The result of the research showed that the reversal of aesthetic structure types in both films happened: firstly, the setting becomes more and more modern, and it is far from savage culture; second, the iconography - weapon and transportation - got modernization; third, both films showed marginal heros; fourth, the story ideas becameome more various and dynamic; and fifth, situations and types of actions become more and more brutal. The evolutions in both Western films were influenced by politization in production process, the age evolution, and the change of audience’s/society’s taste.Degradasi apresiasi terhadap film Western mutakhir melatarbelakangi penelitian ini. Para produser film mencoba merevitalisasi elemen film Western agar menghasilkan karya yang lebih menarik dengan atmosfer yang berbeda. Penelitian ini menelaah invensi dan interaksi budaya melalui eksplorasi unsur-unsur eksternal yang menyebabkan perubahan pada formula genre Western dalam film Wild Wild West (1999) dan Django Unchained (2012). Hasil penelitian ini menunjukkan bahwa terjadi pembalikan tipe struktur estetika dalam kedua film tersebut. Pertama, latar karya menunjukkan ruang yang semakin modern dan cenderung mengurangi ruang kebudayaan liar; kedua, ikon persenjataan dan transportasi yang digunakan oleh para tokoh semakin modern; ketiga, tokoh hero yang ditampilkan semakin marjinal; keempat, ide cerita semakin variatif dan dinamis; kelima, situasi dan pola tindakan yang disuguhkan menunjukkan formula kekerasan yang semakin brutal. Evolusi yang terjadi pada kedua film teranalisis dipengaruhi oleh politisasi produksi, perubahan jaman, dan perubahan selera penonton/masyarakat.